Transforming growth factor‐β promotes the function of HIV‐specific CXCR5+CD8 T cells. (4th May 2020) - Yang, Hong‐Ge; Jiao, Yan‐Mei; Huang, Hui‐Huang; Zhang, Chao; Zhang, Ji‐Yuan; Xu, Ruo‐Nan; Song, Jin‐Wen; Fan, Xing; Jin, Lei; Shi, Ming; Wang, Fu‐Sheng
Abstract: HIV replication can be inhibited by CXCR5 + CD8 T cells (follicular cytotoxic T cell [TFC]) which transfer into B‐cell follicles where latent HIV infection persists. However, how cytokines affect TFC remain unclear. Understanding which cytokines show the ability to affect TFC could be a key strategy toward curing HIV. Similar mechanisms could be used for the growth and transfer of TFCs and follicular helper T (TFH) cells; as a result, we hypothesized that cytokines IL‐6, IL‐21, and transforming growth factor‐β (TGF‐β), which are necessary for the differentiation of TFH cells, could also dictate the development of TFCs. In this work, lymph node mononuclear cells and peripheral blood mononuclear cells from HIV‐infected individuals were cocultured with IL‐6, IL‐21, and TGF‐β. We then carried out T‐cell receptor (TCR) repertoire analysis to compare the differences between CXCR5 – and CXCR5 + CD8 T cells. Our results showed that the percentage and function of TFC can be enhanced by stimulation with TGF‐β. Besides, TGF‐β stimulation enhanced the diversity of TCR and complementarity‐determining region 3 sequences. HIV DNA showed a negative correlation with TFC. The use of TGF‐β to promote the expression of CXCR5 + CD8 T cells could become a new treatment approach for curing HIV.